2023
DOI: 10.1371/journal.pone.0280465
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inspiratory muscle strength and balance in women: A cross-sectional study

Abstract: Background There is scarce evidence on changes at the functional level associated with the respiratory area in women. This study aims to analyse the relationship between inspiratory muscle strength and balance in women. Material and methods In this cross-sectional observational study, the sample consisted of groups according to the results obtained in the balance test. Inspiratory muscle weakness was defined as maximum inspiratory pressure (MIP) ≤ 80% of the predictive value. MIP was carried out using throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The results showed that weaker inspiratory muscle strength tripled the risk of poor performance in balance testing. Early identification of individuals at risk of respiratory muscle weakness or balance impairment is crucial for preventive measures and targeted interventions ( Azevedo et al, 2023 ). Additionally, respiratory system diseases or conditions can also affect MIP ( Raab et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that weaker inspiratory muscle strength tripled the risk of poor performance in balance testing. Early identification of individuals at risk of respiratory muscle weakness or balance impairment is crucial for preventive measures and targeted interventions ( Azevedo et al, 2023 ). Additionally, respiratory system diseases or conditions can also affect MIP ( Raab et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with abdominal obesity, dynapenia, and dynapenic abdominal obesity have impaired respiratory muscle strength [22]. Inspiratory muscle weakness ( 80% predictive MIP) is associated with deficient postural balance in middle-aged and older women [23].…”
Section: Respiratory Sarcopenia and Physical And Nutritional Statusmentioning
confidence: 99%